Measuring Humility in an Indonesian Sample - Melanie Nyhof; Abdul Rahman Shaleh; Rena Latifa; Heri Yulianto (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2021)
Humility has been a neglected virtue in the social and psychological sciences. Owing to the nature of the construct itself, humility poses some special challenges to researchers wishing to assess individual differences. Although there have been significant strides in research in humility, especially in intellectual humility, this research has yet to test measures of humility in non-Western, religious populations. The present study builds on previous research by testing Indonesian versions of humility scales. We measure humility construct based on eight domains identified by Davis and Hook (2014), namely openness/lack of superiority, other-oriented/unselfish, admit mistakes/teachable, interpersonal modesty, accurate view of self, global humility, spiritual humility, and regulate need for status. The data was analyzed using Confirmatory Factor Analysis (CFA) (N=390). Among 44 items theorized to measure Humility, 8 items do not fit the model and are deemed as not valid, while the other 36 items are valid. The recommendation for future research is to further develop the instrument of humility as some factors still have very few items.